Factors affecting the competitiveness of business ideas - Dzhakysheva, U. K. (Journal of Economic Research & Business Administration, 2016)
This paper discusses the problems of competitiveness and the factors affecting the competitiveness of entrepreneurial ideas at this stage. Creating a competitive advantage over rival becomes the strategic focus of the state and its agencies in the field of competitiveness of the national economy. At the same time improving the competitiveness applies to all levels of its hierarchy of products (goods and services), enterprise, industry, region and the country as a whole, but of special importance the company's competitiveness as the main component of the economy. Despite the large number of factors affecting the competitiveness of enterprises, yet basic and crucial of these is its ability to produce competitive products and create the conditions for it to market, its authorities in the field of competitiveness of the national economy. Today, the problem of domestic enterprises improve the competitiveness of products is particularly relevant in view of the fact that the negative impact of economic reforms, largely weakened their position in the domestic and foreign markets.